Policy implementation in independently managed hospitals in Chile: perception of professional hospital staff - Méndez, Claudio; Miranda J., Christian; Torres, M. Cristina; Matthews, Thompson (Revista Chilena de Salud Pública, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--> Introduction: Health reforms have introduced independently managed health care establishments into the health care network. This study explored the perceptions of professional hospital workers with respect to the current stage of policy implementation independently managed establishments, in a high complexity hospital in the south of Chile. Materials and methods: Qualitative single case study based on semi-structured in-depth interviews conducted with health professionals at the San Jose Hospital in the city of Osorno, from August 2010 to December 2011. A sample of 19 professionals was chosen, and the interviews were recorded and transcribed. The analysis was carried out using conventional content analysis. Results: For the interviewees, independent management was conceptualized as autonomy in the decisión making process, with respect to resource distribution and financing. Likewise, recognized weaknesses were related to the absence of organizational capacity and competency within management for implementing changes. According to these professionals, policy options for human resources and for financing of health services provision should be included in order to improve the implementation stage. Discussion: Independent hospital management is conceptualized mainly as financial autonomy. Likewise, implementation has been stalled by persisting gaps between design and implementation in independent hospital management policy. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->